The Enemy - Campo, Rafael (Book collections on Project MUSE., 2007)
In his fifth collection of poetry, the physician and award-winning writer Rafael Campo considers what it means to be the enemy in America today. Using the empathetic medium of a poetry grounded in the sentient physical body we all share, he writes of a country endlessly at war-not only against the presumed enemy abroad but also with its own troubled conscience. Yet whether he is addressing the U.S. invasion of Iraq, the battle against the AIDS pandemic, or the culture wars surrounding the issues of feminism and gay marriage, Campo's compelling poems affirm the notion that hope arises from even the most bitter of conflicts. That hope-manifest here in the Cuban exile's dream of returning to his homeland, in a dying IV drug user's wish for humane medical treatment, in a downcast housewife's desire to express herself meaningfully through art-is that somehow we can be better than ourselves. Through a kaleidoscopic lens of poetic forms, Campo soulfully reveals this greatest of human aspirations as the one sustaining us all.